Oxide Inclusions Removal on Microstructure Properties of As-Cast Cobalt-Based Alloys - Maulana, Muhammad Ilham (Universitas Muhammadiyah Jakarta, 2024)
A cobalt-based metal alloying process was conducted with the addition of the non-metallic element boron (B) using vacuum arc remelting (VAR). The process employed a water-cooled copper mold within an argon atmosphere. This research aimed to investigate the resulting microstructure and surface hardness values of the alloy. The metal melting rate during the VAR process was carefully controlled to achieve the desired microstructure and minimize defects, ensuring the production of high-quality alloys post-solidification. The process effectively facilitated the removal of oxide inclusions through flotation during remelting. The resulting alloy exhibited a dendritic microstructure characterized by large grain sizes. The average hardness value obtained for the alloy was 27.53 HRC.